Augmented Respiratory–Sympathetic Coupling and Hemodynamic Response to Acute Mild Hypoxia in Female Rodents With Chronic Kidney Disease - Saha, Manash; Sun, Qi-Jian; Hildreth, Cara M.; Burke, Peter G. R.; Phillips, Jacqueline K. (Frontiers in Physiology, 2021)
Carotid body feedback and hypoxia may serve to enhance respiratory–sympathetic nerve coupling (respSNA) and act as a driver of increased blood pressure. Using the Lewis polycystic kidney (LPK) rat model of chronic kidney disease, we examined respSNA in adult female rodents with CKD and their response to acute hypoxia or hypercapnia compared to Lewis control animals. Under urethane anesthesia, phrenic nerve activity, splanchnic sympathetic nerve activity (sSNA), and renal sympathetic nerve activity (rSNA) were recorded under baseline conditions and during mild hypoxic or hypercapnic challenges. At baseline, tonic SNA and blood pressure were greater in female LPK rats versus Lewis rats (all P < 0.05) and respSNA was at least two-fold larger [area under the curve (AUC), sSNA: 7.8 ± 1.1 vs. 3.4 ± 0.7 μV s, rSNA: 11.5 ± 3 vs. 4.8 ± 0.7 μV s, LPK vs. Lewis, both P < 0.05]. Mild hypoxia produced a larger pressure response in LPK [Δ mean arterial pressure (MAP) 30 ± 6 vs. 12 ± 6 mmHg] and augmented respSNA (ΔAUC, sSNA: 8.9 ± 3.4 vs. 2 ± 0.7 μV s, rSNA: 6.1 ± 1.2 vs. 3.1 ± 0.7 μV s, LPK vs. Lewis, all P ≤ 0.05). In contrast, central chemoreceptor stimulation produced comparable changes in blood pressure and respSNA (ΔMAP 13 ± 3 vs. 9 ± 5 mmHg; respSNA ΔAUC, sSNA: 2.5 ± 1 vs. 1.3 ± 0.7 μV s, rSNA: 4.2 ± 0.9 vs. 3.5 ± 1.4 μV s, LPK vs. Lewis, all P > 0.05). These results demonstrate that female rats with CKD exhibit heightened respSNA coupling at baseline that is further augmented by mild hypoxia, and not by hypercapnia. This mechanism may be a contributing driver of hypertension in this animal model of CKD.